Acoustic Evaluation of Trabzon Beşirli Central Tennis Court Multi-Purpose Hall - Kandemir, Ayşegül; Kavraz, Mustafa (Fırat University, 2024)
Today, although acoustic designs for different purposes are not realized in sports halls designed for sports activities, these halls are widely used for various events such as conferences and concerts. In this study; The main activity area in the Beşirli Central Tennis Court building, which was built for sports activities within the scope of the European Youth Games in Trabzon Province, was evaluated in terms of acoustics for different functional uses by computer simulation method. First of all, 3D models were prepared for the current conditions of the main sports event areas according to different audience occupancy rates. Then the models were transferred to the simulation program to evaluate the objective parameters of the sound. After obtaining the objective parameter values of the sound, 3D models of the hall were prepared again with the sound-absorbing mechanisms placed between the existing steel structural system on the ceiling plane of the hall, designed for the realization of sports, music and speech activities in the sports activity areas. The prepared 3D models were transferred to the ODEON V10 program and the simulation process was repeated. As a result of all simulations, the values of the objective parameters of the sound obtained for indoor sports activity areas were compared and evaluated with each other and the accepted optimum value ranges.

Günümüzde sportif faaliyetlere yönelik tasarlanmış spor salonlarında farklı kullanım amaçları için akustik tasarımlar gerçekleştirilmemesine rağmen bu salonlar konferans ve konser gibi çeşitli etkinlikler için yaygın şekilde kullanılmaktadır. Bu çalışmada; Trabzon İli, Avrupa Gençlik Oyunları kapsamında sportif etkinlikler için inşa edilen Beşirli Merkez Tenis Kortu binasındaki ana etkinlik alanı bilgisayar simülasyon yöntemi ile farklı fonksiyonel kullanımlar için akustik açısından değerlendirilmiştir. Öncelikle ana spor etkinlik alanlarının mevcut durumları için farklı seyirci doluluk oranlarına göre 3D modelleri hazırlanmıştır. Daha sonra modeller sesin nesnel parametrelerinin değerlendirilmesi için simülasyon programına aktarılmıştır. Sesin nesnel parametre değerleri elde edildikten sonra spor etkinlik alanlarında spor, müzik ve konuşma faaliyetlerinin gerçekleştirilmesine yönelik tasarlanan, salonun tavan düzlemindeki mevcut taşıyıcı elemanların arasına yerleştirilen ses yutucu özellikteki mekanizmalar ile yeniden salona ait 3D modeller hazırlanmıştır. Hazırlanan 3D modeller ODEON V10 programına aktarılarak simülasyon işlemi tekrarlanmıştır. Tüm simülasyonlar sonucunda kapalı spor etkinlik alanları için elde edilen sesin nesnel parametrelerine ilişkin değerler birbirleri ve kabul edilen optimum değer aralıkları ile karşılaştırılmış ve değerlendirilmiştir.
Trabzon Beşirli Merkez Tenis Kortu Çok Amaçlı Salonunun Akustik Değerlendirmesi
Keywords: Architecture (Other); Mimarlık (Diğer)